2004
DOI: 10.1016/s0928-8244(03)00274-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of amplified fragment length polymorphism and pulsed field gel electrophoresis in a hospital outbreak and subsequent endemicity of ampicillin-resistantEnterococcus faecium

Abstract: Reliable molecular methods for determination of relatedness between bacterial isolates have become increasingly important to evaluate outbreaks and endemic situations with nosocomial pathogens. In the present study Simpson's index of diversity with calculated confidence intervals was used to compare amplified fragment length polymorphism (AFLP) and pulsed field gel electrophoresis (PFGE) analysis of a hospital outbreak of ampicillin-resistant Enterococcus faecium and subsequent endemicity. The outbreak, in a N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…Although macrorestriction analysis does not readily establish the degree of genetic relatedness of isolates with substantially different PFGE patterns, it is a highly reproducible typing method that is capable of distinguishing among clonal populations of VRE. Moreover, grouping of isolates by PFGE correlates well with the results obtained by other typing techniques [24,25,32]. In the present study, PFGE identified 32 unique restriction patterns with a similarity ranging from 65% to 98%, which is comparable to the high intra-species genomic variability seen in E. faecium isolates from various sources [33].…”
Section: Discussionsupporting
confidence: 86%
“…Although macrorestriction analysis does not readily establish the degree of genetic relatedness of isolates with substantially different PFGE patterns, it is a highly reproducible typing method that is capable of distinguishing among clonal populations of VRE. Moreover, grouping of isolates by PFGE correlates well with the results obtained by other typing techniques [24,25,32]. In the present study, PFGE identified 32 unique restriction patterns with a similarity ranging from 65% to 98%, which is comparable to the high intra-species genomic variability seen in E. faecium isolates from various sources [33].…”
Section: Discussionsupporting
confidence: 86%
“…Most importantly, though, there were genetic differences between VREF isolated from feces of nonhospitalized persons without infection (genogroup A) and isolates from hospitalized patients of fecal origin or from infected body sites like blood (genogroup C). Other studies confirmed the existence of these genogroups among vancomycin‐susceptible E. faecium (VSEF) isolates originating from different sources (Borgen et al , 2002; Bruinsma et al , 2002; Jureen et al , 2003, 2004; Coque et al , 2005). Furthermore, AFLP exhibited a discriminatory power comparable to PFGE and discriminated outbreak‐related isolates from other isolates (Jureen et al , 2004).…”
Section: Methods To Study the Genetic Relatedness Of E Faeciummentioning
confidence: 71%
“…Three virulence genes, esp , hyl and acm , were also identified by PCR (Vankerckhoven et al., 2004; Camargo et al., 2006). Multilocus sequence typing and pulsed field gel electrophoresis (PFGE) were performed for the genetic comparisons (Jureen et al., 2004; Camargo et al., 2006). Sequence types (STs) and CCs were determined using http://efaecium.mlst.net, and PFGE patterns were analysed with B io N umerics software package v.6.0 (Applied Maths, Sint‐Martens‐Latem, Belgium) using Dice coefficient (optimization, 0.5%; band matching tolerance, 1%) and the unweighted pair group method using arithmetic mean (UPGMA).…”
mentioning
confidence: 99%